Noise pollution in Barranca city -Lima - Perú - Lira-Camargo, Zoila R. (2020)
Several publications report that the health effects of noise pollution are of medical and social importance; causing in people effects such as stress, anxiety, cardiovascular problems, cognitive impairment and decreased physical condition among others. The objective of the investigation was to monitor the sound with measurements in situ in Barranca city, Lima - Peru and to identify the decibels to which some special and commercial protection zones would be subject. The sound recording was done with a sonometer, in the fronts of educational, health center and commercial areas. The results showed that the sound level exceeded the maximum tolerable limit of 50 dB established in Supreme Decree No. 085-2003-PCM, in special in protection areas such as Ventura Ccalamaqui College, Barranca Cajatambo Hospital and mixed areas such as market and commercial center. In conclusion, the noise pollution in the areas evaluated in Barranca city exceeds the established maximum limits, obtaining maximums of 79.32 ± 2.07 dB, especially on the first working day at the beginning of the week; high noise levels would cause adverse effects on people's health.